THE PUBLIC USE OF QUERETARO’S HISTORY: HALF-TRUTHS, LEGITIMACY AND HEGEMONY (Tzintzun, Revista de Estudios Históricos, 2023)
This article exposes the problem of the public use of history by intellectuals. Onthe one hand, we have professionals dedicated to historical research and the resultsof their research; on the other, there are those who will use, reinterpret and disclosethem at their discretion and convenience. Our objective is to analyze the way inwhich Fernando Díaz Ramírez and José Guadalupe Ramírez Álvarez, intellectualsfrom Querétaro of the 20th century, made public use of local history todisseminate their particular vision of the period of government of SaturninoOsornio from Querétaro in the early 1930’s.
Keywords: public use of history; intellectuals; social order; social change; hegemony